Financial Component of the Waste Management System - Yevheniia Ziabina; Stephen Acheampong (Financial Markets, Institutions and Risks)
The article summarizes the arguments and counterarguments within the scientific debate on the development of the waste management system in the context of financial impact. The main goal of the research is to determine the impact of the financial component on the waste management system in Ukraine and the world. The systematization of literary sources and approaches to solving the problem in the waste management system proved that a specific number of publications is published in the subject area - natural sciences. At the same time, it is necessary to pay attention to the fact that the interest in the research topic is constantly growing, especially actively since 2018, which indicates the intensification of the implementation of the Sustainable Development Goals in the world. The urgency of solving this scientific problem lies in the fact that the improvement of the waste management system, the search and implementation of ecologically and economically effective solutions in waste processing require significant financial investments. The study of the issue of the financial component in the waste management system in the article is carried out in the following logical sequence: the first stage – analysis of research relevance based on statistical data; the second stage is a comparative analysis of the dynamics of searches for the keyword "waste management" in the Google search engine using the Google Trends toolkit, in the period from 2004 to 2022 worldwide; the third stage – formation and processing of the research base based on data from the scientometric databases Google Scholar, Scopus and Web of Science; the fourth stage is bibliometric analysis using VOSviewer software version 1.6.19. Systematic, comparative and bibliometric analysis methods became the methodical tools of the conducted research, 2004-2022 was chosen as the research period. Ukraine and other countries of the world were chosen as the object of the study. The article presents the results of a bibliometric analysis on the researched topic, which testified that the dynamics of publishing activity is increasing, the scientific alliances of authors are expanding, which indicates a global level of interest in the search for the most ecologically and economically effective solutions in the waste management system. The study empirically confirms and theoretically proves that the financial component in the waste management system is an integral determinant of influence, which must be taken into account when determining strategic directions for improvement. The results of the conducted research can be useful for further scientific activity on the chosen topic.